The roles of history and habitat area in the distribution and composition of avian species assemblages in the highlands of Costa Rica - Barrantes Montero, Gilbert (2011)
Bird species assemblages in isolated Neotropical highland mountains have been moulded by the drastic climatic changes that occurred in late Pleistocene. Palynological evidence indicates that after the Pleistocene the highlands of Costa Rica and western Panama became isolated as climate turned gradually more tropical and highland vegetation retreated to the upper elevations of high mountains, forming highland islands. We surveyed birds at 10 representative sites throughout the Costa Rican highlands in order to determine the species composition of highland endemic assemblages. The area of available highland habitat explains 77% of the variance in species richness of the 36 highland endemics across highland islands, and the composition of these species assemblages have a nested distribution, rather than beingindependent sets of species on eachisland. The observed nested patternismore consistent with a differential extinction model of species assemblages, and less likely to be explained by differential migration. We conclude that the reduction of highland vegetation and the avifauna associated with it, and its subsequent confinement to the summit of high mountains, is a possible explanation for the current distribution of highland endemic species in Costa Rican highland islands.